Knowledge, awareness, and practice on the usage of pre-emptive analgesia during oral surgical procedures. - Zeeshan Ahsan; Kazmi , Syed Asad Abbas; Siddiqui , Faizan Ahmed; Summaiya Abdul Rehman; Ahsan Inayat (International Journal of Endorsing Health Science Research, 2022)
Background: Pre-emptive analgesia improves patients' quality of life after treatment by reducing post-operative complications and a more rapid return to their daily activities. The current study aims to evaluate knowledge, awareness, and practice on using pre-emptive analgesia during surgical procedures among private dental practitioners in Karachi, Pakistan. Methodology: This survey-based descriptive study was conducted among private dental practitioners working in Karachi, Pakistan. The questionnaire has been designed to assess knowledge, awareness, and practice regarding the usage of pre-emptive analgesia. Part one focused on the socio-demographic characteristics of the participants, including age, gender, and level of experience. While Part two comprises ten multiple-choice questions regarding the knowledge, awareness, and practice of pre-emptive analgesia among private dental practitioners. The survey instrument was a self-administered questionnaire in the English language, and the questionnaire form was sent electronically to the study participants. Results: About 98(74.2%) of participants are aware of pre-emptive analgesia usage during surgical procedures, but only 78(59.1%) practitioners know the mechanism of action of pre-emptive analgesia. While. Diclofenac sodium 35(26.5%) is most commonly used by private dental practitioners as pre-emptive analgesia. Conclusion: The knowledge of oral pre-emptive analgesia was limited among dental practitioners. Most of them know that pre-emptive analgesics are used during oral surgical procedures, but many practitioners don't know their mechanism of action and method of administration.